2022
DOI: 10.3390/membranes12030321
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanocomposite TiSiCN Coatings by Titanium Evaporation and Organosilicon Compound Activation in Hollow Cathode Arc Discharge

Abstract: TiSiCN coatings have been obtained by anode evaporation of titanium and the decomposition of hexamethyldisilazane in an arc discharge, using a self-heated hollow cathode, at the pressure rate of 1 mTorr of the Ar+N2 gas mixture. The proposed method makes it possible to independently and widely change the amount of metal and precursor vapor flows, the pressure and composition of the vapor-gas mixture and the degree of ionic interaction on the surface of the growing coating within a single discharge system. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The experiments were carried out in a discharge system based on a discharge with an SHHC, the scheme of which is shown in Figure 1, and the design of the system is described in detail in [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were carried out in a discharge system based on a discharge with an SHHC, the scheme of which is shown in Figure 1, and the design of the system is described in detail in [28].…”
Section: Methodsmentioning
confidence: 99%
“…The disadvantages above describe the deprivation of obtaining coatings by reactive anodic evaporation of titanium and decomposition of an OSC precursor in a discharge with a self-heating hollow cathode (SHHC). The possibility of obtaining TiSiCN coatings by the proposed method was realized in [28], where the results of the first experiments are presented, showing the fundamental possibility of obtaining nanocomposite TiSiCN coatings by this method. In such a discharge, a high-density plasma is created without using a separate source of vapor-gas mixture ionization, and filtration systems are not used, since there are no microdrops in the vaporized metal stream.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were carried out on the installation schematically shown in Figure 1. The design of the gas discharge system and the experimental scheme are described in detail in [4]. The gas discharge system is equipped with a hollow cylindrical cathode made of TiN powder by magnetic pulse pressing and a sectional anode.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…They may have excellent performance characteristics, but the properties of these coatings are determined mainly by the conditions of their synthesis. In [4], a method for obtaining TiSiCN coatings by anodic evaporation of titanium and decomposition of hexamethyldisilazane (HMDS) in hollow cathode arc discharge was described. The advantage of this method is the ability to independently change various deposition conditions over a wide range, in particular the metal vapor flow, discharge current, composition and pressure of the gas mixture.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain binary coatings by reactive evaporation, arcs with a self-heating hollow cathode (SHC) are used, which are able to function stably for a long time under conditions of pumping an inert gas (or N2) through the cathode cavity and supplying the reaction gas to the discharge gap [2], both in continuous and pulse-periodic (10-1000 Hz, 10-100 ms) modes [3]. Oxide [4], nitride [5], and composite [6] coatings are obtained by reaction anode evaporation in a discharge with SHC at a rate of more than 1 μm/h.…”
Section: Introductionmentioning
confidence: 99%